THE CONCEPT OF FAMILY IN ISLAM: Equality of Husband and Wife in the Kitab Adabul Mu’asyaroh by KH. Achmad Yasin Asmuni - Millatuz Zakiyah; Yulianto, Yulianto; Fitriana, Rahma; Husniyah, Af'idatul (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2024)
ABSTRACT The kitab munakahat so far only presents Islamic procedures for intercourse, the wife's obligations to her husband, or the husband's rights to his wife which are full of patriarchal nuances. Different from other classical Islamic books, the Kitab Adabul Muasyaroh by KH. Yasin Asmuni offers mutuality in marriage towards a saadah marriage as in the marriage of the Prophet Muhammad and Khadijah al Kubro. This study focuses on describing the concept of saadah marriage in the Kitab Adabul Muasyarah using a critical discourse approach. The results of the study show that in terms of text, there are rewording, overwording, euphemisms, and metaphors; intertextually it was found that the thoughts of KH. Yasin Asmuni in this book were influenced by two Islamic thinkers, namely Abu Hamid Al Ghazali and Jamaluddin al-Qosimi. The justice of the division of rights and obligations of husband and wife in this book uses the mubadalah 'mutual' approach which is in line with the reading of Faqihuddin Abdul Kodir’s theory of Mubadalah which was published twenty years after this book was published. Explanatively, it is found that this book positions husband and wife proportionally as evidenced by the existence of obligations and rights for husband and wife. Another uniqueness of this book is the existence of a contradiction in thought in the form of the husband's dominance over his wife in the early part and the mutuality and equality of husband and wife in the middle to the end of the Kitab Adabul Muasyaroh because this book is a kitab khulasah that combines the thoughts of two Islamic thinkers, occurs. ABSTRAK Kitab munakahat selama ini hanya menyajikan tata cara bersenggama yang Islami, kewajiban istri atas suami, atau hak suami atas istri yang sarat nuansa patriarkal. Berbeda dengan kitab lain, Kitab Adabul Muasyaroh karya KH. Yasin Asmuni menawarkan kesalingan dalam pernikahan menuju pernikahan saadah sebagaimana pernikahan Nabi Muhammad dan Khadijah. Kubro. Penelitian ini fokus mendeskripsikan konsep pernikahan saadah dalam Kitab Adabul Muasyarah dengan pendekatan wacana kritis. Hasil penelitian menunjukkan secara teks, terdapat rewording, overwording, eufimisme, dan metafora; secara intertekstual ditemukan bahwa pemikiran KH. Yasin Asmuni pada kitab ini dipengaruhi dua pemikir Islam, yaitu Abu Hamid Al Ghazali dan Jamaluddin al-Qosimi. Keadilan pembagian hak dan kewajiban suami dan istri dalam kitab ini menggunakan pendekatan mubadalah ‘kesalingan’ yang selaras dengan pembacaan Mubadalah Faqihuddin Abdul Kodir yang terbit dua puluh tahun setelah kitab ini terbit. Secara eksplanatif, ditemukan bahwa kitab ini memosisikan suami dan istri secara proporsional terbukti dengan adanya kewajiban dan hak bagi suami dan istri. Keunikan lain dari kitab ini adalah adanya kontradiksi pemikiran berupa dominasi suami atas istri pada bagian awal dan kesalingan dan kesetaran suami dan istri pada bagian tengah hingga akhir Kitab Adabul Muasyaroh ini karena kitab ini merupakan kitab khulasah yang memadukan pemikiran dua pemikir Islam, terjadi.